MINORITISASI AHMADIYAH DI INDONESIA - Mudzakkir, Amin (Masyarakat Indonesia, 2011)
This article shows the process of minoritization of Ahmadiyya in Indonesia. This is a phenomenon of the post-Suharto regime. Under the current Indonesia’s liberal democratic system, the existence of minority groups is often marginalized because they are considered not important for political party to win the election. Minoritization occurs when two conditions are met, namely the strengthening of radical Islamic groups and the seemingly indecisive behavior of government to deal with radicalism. The paper critically looks at the current Indonesia political system in order to look for solution to the Ahmadiyya issue.